Nickel-based nanocatalysts promoted over MgO-modified SBA-16 for dry reforming of methane for syngas production: Impact of support and promoters - Taherian, Zahra; Khataee, Alireza; Orooji, Yasin (Elsevier Sci Ltd, 2021)
A series of Ni/SBA-16-MgO catalysts with varying promoters (3 wt% of Y, Ce, and La) were provided through a double-solvent way and tested in reforming of CH4 with CO2 process. The characterization was done using XRD, BET, TPR, and HRTEM for unused catalysts and via TPO, HRTEM, and FESEM equipped with EDX techniques for used catalysts. Among unpromoted and promoted catalysts, the Y-promoted catalyst resulted in the smallest Ni particles (11.5 nm) within the MgO-modified SBA-16, highest Ni dispersion, and oxygen vacancies. The catalytic results illustrated that adding Y and Ce promoters had a positive effect on the catalytic activity and stability (especially for Y-promoted catalyst) while adding La indicated a negative influence because of larger Ni crystallite size and agglomeration. The TPO, HRTEM, and FESEM observations illustrated the deposition of tip type nanotubes carbon on the catalysts surface that was greater on the unpromoted catalyst surface. (C) 2021 Energy Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: Reforming of CH4 with CO2; Modified SBA-16; Ni catalyst; Cerium; Yttrium